The grain crops as activities for the development and integration of the great dourados region to the national productive circle - Guedes da Silva, Walter (2012)
Led to become a national productive Center, the Great Dourados Region, which consists of 40 cities located in the south of the state of Mato Grosso do Sul – Brazil, emerged as a grain productive region from the middle of the 1970s in the 20th century to the beginning of the 21st century. Using modern agricultural techniques, the land organization in this region was ruled by a development policy which was not concerned with the socio-environmental aspects of the area. In this context, the present work aims to analyze the development process of the Great Dourados region, through soybean production and its relation to the confinement of the indigenous people present in the Area. This integration happened due to the money and for it, inserting this Region into a national productive pattern which guided the farmers to modern crops, mainly soybean. The land cultivation was not the only productive activity that granted the Region an economic integration, to both the national and international market. From the end of the Paraguay War (1870) to the middle of the 70s, there were at least two other ways to the regional economic integration. One of them happened with the traditional activities of cattle raising and the extraction of the Paraguay tea (maté/ Yerba Mate) from 1870 to 1937, which divided the regional territory into large farmlands focused on the external market. The other way happened with the need to create a market for the agricultural production and for the demand for manufactured goods, which reorganized the regional territory into small farmlands, as a result of colonization projects from 1943 to 1956. Since 1976, with the creation of the Special Program for the Development of the Great Dourados Region (Prodegran), the capitalist relations of production, which were consolidated in the area, were not ruled almost exclusively by the traditional activities of cattle raising and the extraction of the Paraguay tea, in order to create a new accumulation center connected to the modern crops. As this new accumulation center was created, the Region was led to a selective and dependent integration process, in which many farmers changed their accumulation centers to modern grain crops, causing environmental degradation, productive exclusion and ethnical-cultural conflicts with the indigenous community.